The Relationship Between Glycemic Control And Lipid Profile In Patients With Type 2 Diabetes Mellitus In Bangli Hospital - Pradnyani, Made A.A.; Sutarjana, I Ketut (Syntax Corporation Indonesia, 2024)
Diabetes Mellitus (DM) type 2 is susceptible to diabetic dyslipidemia, which is one of the factors in increasing the risk of complications from cardiovascular disease. The aim of this study was to determine the relationship between glycemic control and lipid profile in type 2 DM patients. A cross-sectional study was conducted at the Internal Medicine Polyclinic at Bangli Regional Hospital for the period January 2023-December 2023 and a total of 60 type 2 DM patients met the inclusion criteria. Patients were grouped into type 2 DM patients with controlled glycemic control (HbA1c < 7%) and uncontrolled (HbA1c≥7%). Lower levels of total cholesterol (160,444 ± 30,608 mg/dl vs 203,476 ± 45,471 mg/dl; p= 0.001), triglycerides (125,500 ± 56,019 vs 202,047 ± 91,568; p= 0.002), low-density lipoprotein (K-LDL ) (93,072 ± 28,443 vs 131,571 ± 44,590; p= 0.001) in type 2 DM patients with good glycemic control. High-density lipoprotein (K-HDL) levels (50,022 ± 14,050 vs 41,152 ± 12,619; p = 0.019) were higher in type 2 DM patients with good glycemic control. From statistical tests, a positive correlation was found between total cholesterol levels (r = 0.277; p = 0.032), triglycerides (r = 0.386; p = 0.002) and K-LDL (r = 0.357; p = 0.005) with HbA1c levels. There is a negative correlation between K-HDL (r=-0.366; p = 0.004) and HbA1c levels. The significant correlation between HbA1c and lipid profile shows the importance of glycemic control in type 2 DM patients. This can be explained in the pathogenesis of type 2 DM in the advanced phase. There is a positive correlation between glycemic control (HbA1c) and total cholesterol, triglycerides and K-LDL. There is a negative correlation between glycemic control (HbA1c) and K-HDL.